Solve the following system of Diophantine equations(the unknowns are positive integers):
$$ \left\{ \begin{array}{c} x^2+3y=u^2 \\ y^2+3x=v^2 \end{array} \right. $$

I worked as follows:
subtract the two equations to get: $4x^2-4y^2-12(x-y)=9y^2-9x^2\ \implies\ ... (x-y)(13x+13y-12)=0\implies x=y\ or\ 13x+13y-12=0$
The first equation has infinite answers and the second has none(since $gcd(13,13)$ does not divide $12$), am I right??

  • $\begingroup$ Shouldn't subtraction give you $x^2 + 3y - y^2 - 3x = u^2 - v^2$? $\endgroup$ – An Hoa Jun 13 '16 at 2:57
  • $\begingroup$ @AnHoa Yes you are right,but before that I had deduced that since $u^2-x^2=3y$ so $u-x=3$ and $u+x=y$ $\endgroup$ – Hamid Reza Ebrahimi Jun 13 '16 at 3:37

We can without (much) loss of generality assume that $y\le x$. Note that $x^2+3y$ is a perfect square greater than $x^2$.

Thus we have $x^2+3y\ge (x+1)^2$. But $x^2+3y\lt (x+2)^2$. It follows that $3y=2x+1$.

Since $y^2+3x$ is a perfect square, so is $9y^2+27x$, that is, $4x^2+31x+1$. This has to be a square, so $4x^2+31x+1$ is equal to one of $(2x+1)^2$ or $(2x+2)^2$ and so on up to $(2x+7)^2$, since $(2x+8)^2$ is clearly too big.

The case $(2x+1)^2$ does not work, and neither does $(2x+2)^2$, nor $(2x+3)^2$. The case $(2x+4)^2$ gives $x=1$. The case $(2x+5)^2$ does not work. The case $(2x+6)^2$ gives $x=5$, which does not work because $y$ is not an integer, and the case $(2x+7)^2$ gives $x=16$.

We conclude that the solutions are $x=1,y=1$, $x=16, y=11$, (and $x=11,y=16$).

  • $\begingroup$ It seems there are other answers for unknowns too,for example: $x=16,y=11,u=17,v=13x=16,y=11,u=17,v=13$... – $\endgroup$ – Hamid Reza Ebrahimi Jun 13 '16 at 4:01
  • $\begingroup$ @HamidRezaEbrahimi: My approach used a few more cases than perhaps necessary, but I think things are OK now. $\endgroup$ – André Nicolas Jun 13 '16 at 5:02

The solution to this system of equations there. http://www.artofproblemsolving.com/community/c3046h1046718__4


Use this decision.






In our case, it is necessary to $b=1$ ; $p=1$ and $(a,s) - (\pm3;\pm1)$


$$x^2-y^2-3(x-y)=u^2-v^2$$ $$(x-y)(x+y-3)=(u+v)(u-v)$$ Assuming $u^2-v^2\neq 0$, we have: $$\dfrac{x-y}{u-v}=\dfrac{u+v}{x+y-3}=\dfrac{r}{s}$$ where $\gcd(r,s)=1$. $$x-y=\dfrac{r(u-v)}{s}$$ $$x+y=\dfrac{s(u+v)}{r}+3$$ since $x,y$ are integers, and $u,v$ have the same parity, then there exist $p,q$ such that: $$u-v=ps $$ $$ u+v=qr $$ Hence, $$x-y=pr $$ $$x+y=qs+3 $$ with $$x=\dfrac{qs+pr+3}{2}$$ $$y=\dfrac{qs-pr+3}{2}$$ $$u=\dfrac{qr+ps}{2} $$ $$v=\dfrac{qr-ps}{2} $$ where either $qr$ and $ps$ have the same parity and $pr$ and $qs$ have opposite parity.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.